2016
DOI: 10.2147/ndt.s118058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dissociation on treatment of depressive and anxiety spectrum disorders with and without personality disorders

Abstract: ObjectiveThe central goal of the study was to analyze the impact of dissociation on the treatment effectiveness in patients with anxiety/neurotic spectrum and depressive disorders with or without comorbid personality disorders.MethodsThe research sample consisted of inpatients who were hospitalized in the psychiatric department and met the ICD-10 criteria for diagnosis of depressive disorder, panic disorder, generalized anxiety disorder, mixed anxiety–depressive disorder, agoraphobia, social phobia, obsessive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 76 publications
(68 reference statements)
1
15
0
Order By: Relevance
“…The correlation coefficients between the relative objCGI and the initial anxiety, depressive, and dissociation levels were negligible, and the mediation model did not prove their role in the process. Based on previous research, 9 , 10 we found that the relative change of the objCGI was influenced by a number of quite small predictors (ranging from clinical, such as initial disorder severity, to psychological, like dissociation) which together mildly predicted the therapeutic outcome. This study concluded with same results as well.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The correlation coefficients between the relative objCGI and the initial anxiety, depressive, and dissociation levels were negligible, and the mediation model did not prove their role in the process. Based on previous research, 9 , 10 we found that the relative change of the objCGI was influenced by a number of quite small predictors (ranging from clinical, such as initial disorder severity, to psychological, like dissociation) which together mildly predicted the therapeutic outcome. This study concluded with same results as well.…”
Section: Discussionmentioning
confidence: 77%
“…The CBT program included therapeutic activities such as psychoeducation, case conceptualization, work with automatic thoughts and schemas, exposures, and problem-solving. 10 Short psychodynamic therapy concentrated on relational problems in a patient’s life and group interactions, which were both related to a person’s development. The program for both groups was supplemented with assertive training, mental imagery, relaxation, sport, and ergotherapy.…”
Section: Sample and Methodsmentioning
confidence: 99%
See 3 more Smart Citations